Antifungal activity of ε-poly-L-lysine on Trichothecium roseum in vitro and its mechanisms. (August 2018) - Wei, Meilin; Ge, Yonghong; Li, Canying; Chen, Yanru; Wang, Wenhui; Duan, Bin; Li, Xue
Abstract: Trichothecium roseum is the main pathogen that causes postharvest decay in several fruits and vegetables. ε-poly-L-lysine (PL), generally regarded as a safe (GRAS) substance, is a cationic homopolymer that consists of ε-amino and α-hydroxyl. The effect of PL at different concentrations (0, 12.5, 25. 50, 100, and 200 μL L −1 ) on the mycelia growth and spore germination of T. roseum was investigated in this study. The mechanisms of PL inhibition on T. roseum growth were also studied. The results indicated that the mycelia growth and spore germination of T. roseum were significantly inhibited at 100 and 200 μL L −1  PL. Electrical conductivity and extracellular protein showed that PL treatment destroyed the plasma membrane integrity of the mycelia and spores, respectively, and decreased extracellular malondialdehyde (MDA) and sugar content after treatment. Scanning electron microscopy indicated that PL treatment damaged spore morphology, and the surface was rough and shrinking. Transmission electron microscopy indicated that PL severely destroyed the cell wall and the plasma membrane of the T. roseum spore, leading to the loss of cytoplasm and cracking of vacuole. These results suggest that PL effectively inhibits the growth of T. roseum, and the mechanism is related to the damage of cell walls and cell membranes. Highlights: ε-poly-L-lysine (PL) directly inhibited the growth of T. roseum. PL caused the damage to cell wall and plasma membrane of T. roseum. Inhibition of T. roseum by PL is related to the damage of cell membrane.